Alumni Engagement measurement and Impact: Benchmarking for success - Jain, Yashraj (ICAReAlumni Conference Proceedings, 2019)
ntroduction and aim:CASE conducted research across 140 institutions across 27 countries from Europe and Asia-Pacific to better understand the state of alumni relations across the globe with the aim of answering two basic questions:1. What are we giving to our alumni communities? How do we provide support that is helpful and meaningful?2. In turn, what are our alumni giving to our institutions? How is that support enabling our missions? Are we making the most of their support?This data has enabled us to create a framework to measure metrics for alumni relations in a robust and standardised manner.• Research methodology:CASE conducted an institutional survey of 140 institutions in Europe and Asia-Pacific that have active alumni relations programmes. The survey was administered 2017 and collected data corresponding to 2016-2017. The data was queried and verified following a rigorous set of arithmetic, logic, ratio and substantive checks. Monetary data collected was converted into GBP as the base currency for Europe and AUD as the base currency for Asia-Pacific. The insights from the data were triangulated with nominations and award winners from the CASE Circle of Excellence awards and this overlay of quantitative and qualitative data truly brought the findings to life. A consolidated report was published in October 2018.Another pilot study was run with seven institutions to test the framework that was developed to alumni relations metrics in 2015, 2016 and 2017.• Results and implications:The results have implications in the following areas:- Defining key metrics and terms in alumni relations impact and measurement- Facilitate development of frameworks and models in alumni relations- Enable alumni relations practitioners to apply the research findings in a practicable and actionable manner• Conclusion:Based on the findings we now know the impact of engaging alumni on achieving an institution’s strategic goals (usually focused on recruitment, teaching and the student experience and research) and the impact on the success and fulfilment of alumni themselves.The findings throw light on strategic alumni relations planning by offering insights into decision making in alumni relations programming.The presentation will also focus on the benefits of alumni advocacy supporting reputation and other non-financial considerations. Examples will be presented from institutions across the globe that have successfully used their alumni to build and manage brand reputation.Lastly, it presents a toolkit to justify and bid for resources to carry out the vital work alumni relations professionals do to demonstrate why giving the sector more funding results in more positive outcomes for our institutions.